Correlation Between Eye Aperture Diameter and Complications in the Posterior Eye Segment after Nd-Yag Capsulotomy - Emina Alimanović Halilović (Biomolecules & Biomedicine, 2008)
The aim of our research was to explore possible correlation between eye aperture diameter and occurrence of complications in the posterior eye segment after Nd-YAG capsulotomy. In the study, we analyzed 120 eyes of the patients who experienced opacities in the posterior capsule or developed secondary cataract after the surgery. All patients underwent Nd-YAG laser posterior capsulotomy. Thereafter, we monitored complications occurrence in the posterior eye segment in intervals of one hour, seven days, one month and six months following the surgery. The frequency of complications increased with time. Six months after Nd-YAG laser posterior capsulotomy we found changes in the posterior eye segment: hole in the anterior hyaloid membrane in case of 9 (7,50%) eyes, prolapse of the corpus vitrei in 2 (1,66%) cases, retinal hole in case of 5 (4,16%) eyes, macular hole in 3 (2,50%) eyes, retinal detachment in 3 (2,50%) eyes, cystoid macular edema in 2 (1,66%) eyes, (1,66%), and macular pack in case of 11 (9,16%) eyes. Aperture size in the posterior capsule directly correlates with the number of complications. We suggest that the aperture diameter should not exceed 4,0 mm.